(untitled) (Journal of Nepal Physical Society, 2021)
We present the distribution of dust color temperature, Planck’s function, dust mass, and visual extinction in the far-infrared (140 μm and 90 μm) AKARI surveys of the Crab Nebula using Sky View Virtual Observatory. With a systematic search of a supernova remnants, we found Crab Nebula at R. A. (J2000) / Decl. (J2000) = 05h 34’ 31.94"/+22° 00’ 52.20". The maximum flux is found to be 145.94 MJysr-1 at 140 μm and 177.01 MJysr-1 at 90 μm wavelength. The total dust mass of the Supernova remnant is estimated to be 6.11×1039 kg (3.07×109 Mʘ) and the dust color temperature is found in the range between 31.16 K to 47.11 K with mean value of temperature of 38.07 K. Similarly we obtained the value of Planck’s function in the range of 3.96 × 10-15 Wm-2sr-1Hz-1 to 1.96 × 10-14 Wm-2sr-1Hz-1 with average value 9.59 × 10-15 Wm-2sr-1Hz-1. The value of visual extinction ranges from 9.21 × 10-14 mag to 2.70 × 10-13 mag with mean value of 1.57 × 10-13 mag. The distribution trend of flux, dust color temperature, and Planck’s function are nearly similar, whereas dust mass and visual extinction follow an inverse relationship with the previous three parameters.